Experimental Study on Wind Acceleration Effect in Wind Farms with Complex Terrain - Xiaosheng YAN; Yue LI; Xiaoxia GAO; Xi WANG (Zhongguo dianli)
Sloping land makes the speed of the inflow on the flat land increase after a certain height difference, which results in the wind acceleration effect. Experiments were conducted in a mountain wind farm to obtain the flow field data of the slope wind field and study the influence of slope terrain on the wind acceleration effect. Experimental results show that the acceleration effect is related to the altitude of the slope, and the measured acceleration ratio at high altitudes is only about 16.9% of that predicted by Taylor’s original algorithm. Moreover, both the slope and the wind direction are also factors affecting the acceleration effect. Generally, the acceleration effect becomes more prominent when the slope is greater. In this experiment, the acceleration ratio in the positions with a larger slope is increased by 61.6%, and the acceleration ratio on the crosswind side of the slope is about 10% larger than that on the windward side. Meanwhile, the reasons for errors generated by Taylor’s original algorithm are analyzed, and the modified formula of Taylor’s method suitable for complex terrain is proposed in this paper.